1990
DOI: 10.1111/j.1472-765x.1990.tb00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of oregano and thyme essential oils on moulds and foodborne bacteria

Abstract: The essential oil of oregano (‘origanum oil’; thymol type oil from Origanum vulgare) inhibited completely the mycelial growth of Aspergillus niger and A. flaous at 400 μg/ml, while A. ochraceus was inhibited at 600 μg/ml. At 700 μg/ml, thyme oil inhibited the mycelial growth of A. flavus and A. niger but not that of A. ochraceus. Fungal spore germination was inhibited by 600 μg/ml of origanum oil and (with the exception of A. ochraceus) by 700 μg/ml of thyme oil. Under aerobic conditions, the essential oils of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(89 citation statements)
references
References 9 publications
4
76
0
9
Order By: Relevance
“…Although many plants and herbs have been reported to have antimicrobial activity against food-borne pathogens, [6][7][8] our results provide another herb of choice for fighting these pathogens. The possibility of developing bacterial resistance to plants and plant products 5,19) has sent the message to scientists to add more to the list of plants and plant products inhibiting food-borne pathogens.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although many plants and herbs have been reported to have antimicrobial activity against food-borne pathogens, [6][7][8] our results provide another herb of choice for fighting these pathogens. The possibility of developing bacterial resistance to plants and plant products 5,19) has sent the message to scientists to add more to the list of plants and plant products inhibiting food-borne pathogens.…”
Section: Discussionmentioning
confidence: 95%
“…Plants and herbs are among the potential options because of their natural origin and antimicrobial activity. [6][7][8][9][10][11][12] Chives (Allium schoenoprasum) are bulb-forming herbaceous perennial plants belonging, together with garlic, onion, shallot and leek, to the Alliaceae family. They can be easily grown with little care and found fresh throughout Thailand all year-round.…”
mentioning
confidence: 99%
“…Moreover, thyme essential oil and its main components have been also reported for fungicidal and antibacterial activities (Panizzi et al, 1993;Muller-Ribeau et al, 1995;Janssen et al, 1987;Kurita et al, 1981;Paster et al, 1990;Daferera et al, 2000;, but showed also herbicidal effects (Angelini et al, 2003;Tworkoski, 2002) and insecticidal properties (Duke et al, 1992;Regnault-Roger et al, 1993). As a mechanism of interruption of nervous system was found for thymol and carvacrol in insects (Ryan & Byrne, 1988), a similar mode of action could be supposed for the nematicidal action of thyme (Korayem et al, 1993).…”
Section: -mentioning
confidence: 99%
“…Más de 280 especies han sido investigadas por sus efectos tóxicos, de las cuales cien han demostrado alguna actividad sobre el crecimiento de hongos (Montes y Carvajal, 1998), como Aspergillus niger, A. ochraceus, A. flavus, Eurotium sp., entre otros (Sharma y Tripathi, 2008). El aceite de orégano, tomillo, clavos, ajo, perejil, apio, entre otros, han demostrado actividad antimicrobiana (Paster et al, 1990;Barrera y García, 2008, Mora et al, 2001, Carrillo et al, 2010Alzate et al, 2009). En naranjas Valencia, Navel y Navelate, se han encontrado compuestos que son escasos en otras plantas y causan inhibición en hongos como el Penicillium digiatum (Ortuño et al, 2006).…”
Section: Introductionunclassified